EFISIENSI USAHATANI TANAMAN SAWI - Umi Rofiatin (Universitas Tribhuwana Tunggadewi, 2010)
Mustart is one of important vegetable crops because is it because so many function for menu and as food. The other important thing is so many vitameins and minerals contents in this rops usefull for the human body. The aims of this research is to determine cost of production, income and efficieny of fam analysis. Location of the reaserach is at Centre of Agriculture Traning and Village Independent, Tulungrejo, Batu City. Data primer and secunder was collected with simple statistic analysis data was used. Research result showed that cost analysis farming of mustard is Rp 1.841.7000 each sowing season, with price is Rp. 5.000/kg. Cost of farming is Rp. 3.000.000 with farmer income Rp. 1.158.300. Mustart farming systems is effisien with beneficial ratio is 1,63 . Beneficial price is Rp. 3.070/kg with beneficial product about 368,34 kg. All figure is under standart price and riil production